Proceedings of the 4th World Sustainability Forum 2014
DOI: 10.3390/wsf-4-f009
|View full text |Cite
|
Sign up to set email alerts
|

Multitemporal Analysis of Thermal Distribution Characteristics for Urban Heat Islands Management

Abstract: For a reliable assessment of sustainability in big cities, it is imperative to evaluate urban ecosystem conditions and the environment of the cities undergoing economic growth. Urban green spaces are valuable sources of evapotranspiration, which is generated by trees and vegetation; these spaces mitigate urban heat islands in cities. Land surface temperature (LST) is closely related to the distribution of land-use and land-cover characteristics and can be used as an indicator of urban environment conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Urbanization and related anthropogenic activities are causing myriad environmental changes (Grimmond, 2007;Imhoff et al, 2010;Gusso et al, 2014;Nyamekye et al, 2020). Among the changes are land use and land cover (LULC) transformations that alter the near-surface thermal characteristics (e.g., Mbithi et al, 2010;Amiri et al, 2009;Uddin et al, 2010;Nurwanda and Honjo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization and related anthropogenic activities are causing myriad environmental changes (Grimmond, 2007;Imhoff et al, 2010;Gusso et al, 2014;Nyamekye et al, 2020). Among the changes are land use and land cover (LULC) transformations that alter the near-surface thermal characteristics (e.g., Mbithi et al, 2010;Amiri et al, 2009;Uddin et al, 2010;Nurwanda and Honjo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated that cities are growing and increasing so much in developing countries in Africa [7][8][9][10]. The studies have shown a withdrawal of vegetation cover in areas near the peripheries of the cities while the built fabric is expanding.…”
Section: Introductionmentioning
confidence: 99%
“…SUHI can occur when buildings and pavement exist instead of vegetation and tree canopies causing anthropogenic heat release [4]. Construction material such as concrete and asphalt used in urban areas does not allow water to stick to the soil causing LST to rise [5]. With the population in urban areas growing, it is estimated that 66% of the total population will be living in urban areas by 2050 [6] and as a result, issues relating to urban heat are becoming more important.…”
Section: Introductionmentioning
confidence: 99%